A novel method for resonant inelastic soft X‐ray scattering via photoelectron spectroscopy detection. (5th October 2017) - Dakovski, Georgi L.; Lin, Ming-Fu; Damiani, Daniel S.; Schlotter, William F.; Turner, Joshua J.; Nordlund, Dennis; Ogasawara, Hirohito
Abstract : A description of the concept and first test of a photoelectron‐based method for measuring inelastic X‐ray scattering is given. Abstract : A method for measuring resonant inelastic X‐ray scattering based on the conversion of X‐ray photons into photoelectrons is presented. The setup is compact, relies on commercially available detectors, and offers significant flexibility. This method is demonstrated at the Linac Coherent Light Source with ∼0.5 eV resolution at the cobalt L 3 ‐edge, with signal rates comparable with traditional grating spectrometers.